2017
DOI: 10.1016/j.bpj.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Focal Adhesion Substructures by Localization Microscopy

Abstract: Cells rely on focal adhesions (FAs) to carry out a variety of important tasks, including motion, environmental sensing, and adhesion to the extracellular matrix. Although attaining a fundamental characterization of FAs is a compelling goal, their extensive complexity and small size, which can be below the diffraction limit, have hindered a full understanding. In this study we have used single-molecule localization microscopy (SMLM) to investigate integrin b3 and paxillin in rat embryonic fibroblasts growing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…The generation and maintenance of such high-force ligand−integrin interactions require that ligands are spaced less than 58 nm apart 23 . In our experiments, the location of mature focal adhesion within a NIH-3T3 cell did not correlate with the positioning of the RGD peptides beneath the spread cells suggesting that once cells adhered and spread, a cell-intrinsic process such as actin-generated forces takes over to form mature adhesion structures with a complex molecular suborganisation 37 . SMLM imaging of both protein clustering in adherent cells on model surfaces and the distribution and location of ligands beneath the cells could thus reveal insights into adhesion biology that may have been obscured when surface characterisation and cell adhesion are examined separately.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The generation and maintenance of such high-force ligand−integrin interactions require that ligands are spaced less than 58 nm apart 23 . In our experiments, the location of mature focal adhesion within a NIH-3T3 cell did not correlate with the positioning of the RGD peptides beneath the spread cells suggesting that once cells adhered and spread, a cell-intrinsic process such as actin-generated forces takes over to form mature adhesion structures with a complex molecular suborganisation 37 . SMLM imaging of both protein clustering in adherent cells on model surfaces and the distribution and location of ligands beneath the cells could thus reveal insights into adhesion biology that may have been obscured when surface characterisation and cell adhesion are examined separately.…”
Section: Discussioncontrasting
confidence: 60%
“…3 ). Since it was previously reported that mature adhesions are not homogenous clusters, but consist of substructures within a mature adhesion 37 , 39 , we first identified adhesive structures in total internal reflection fluorescence (TIRF) images and then quantified the properties of paxillin-mEos2 clusters within these adhesive structures after segmentation by DBSCAN 34 , 35 . This afforded us the opportunity to compare the cluster morphology of paxillin-mEos2 in adhesive structures induced by RGD-A647 peptides compared to RGD peptides without the fluorophore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DBSCAN is able to define clusters and deal with noise, in literature alternative clustering algorithms have been proposed that work better for certain biological samples. Examples are Voronoi tessellation, Bayesian cluster identification and the use of a Gaussian-mixture model [13, 2830]. A comparison of our KDE and DBSCAN implementations with clustering algorithms by Voronoi tessellation [13, 17] and Bayesian statistics [29] can be found in Additional file 2: Figure S2.…”
Section: Methodsmentioning
confidence: 99%
“…The main reason is that existing SMLM techniques require cluster analysis tools, which have been developed for relatively simple cases, such as membrane protein clusters without strong heterogeneity in size, shape, and density (Nicovich et al, 2017;Nieves and Owen, 2020). Several studies have addressed this by designing novel approaches to investigate the inner architecture of NAs and FAs, such as one based on the expectation-maximization of a Gaussian mixture (EMGM) (Deschout et al, 2017). The imagining was carried out on specifically bio-functionalized substrates, on which ordered patterns of nanoscale adhesive spots were provided (Arnold et al, 2004).…”
Section: Formation Of Integrin Clustersmentioning
confidence: 99%